Adaptive Responses Account for the β-Curve-Hormesis is Linked to Acquired Tolerance - A. R. D. Stebbing (SAGE Publishing, 2003)
To date there is no single shared property of the various physical and chemical agents that elicit the β-curve to account for its form, leading to the proposition that hormesis is a consequence of the nonspecificity of adaptive responses. It is argued that adaptive responses to toxic agents may be expected to follow the β-curve. Four kinds of examples are reviewed (enzyme activity, sequestration and repair, and reproductive and homeostatic responses) that corroborate this proposition. The homeostasis example (incorporating homeorhesis) is considered in more detail, using the author's published hydroid experimental growth data, to show that both the α-and β-curves are satisfactorily explained in this way. Many consider that hormesis is merely due to regulatory overcorrections, but it is proposed that it is a consequence of adaptations of the rate-sensitive growth control mechanism (homeorhesis) to sustained levels of inhibition to which the growth control mechanism adapts. In response to low levels of inhibition, upward adjustment of preferred growth rates confers greater resistance to inhibition, with growth hormesis as a cumulative byproduct.